1988
DOI: 10.1021/bi00416a005
|View full text |Cite
|
Sign up to set email alerts
|

Electron-transfer events near the reaction center in oxygen-evolving photosystem II preparations

Abstract: 1985)]. This species was first observed by use of electron spin resonance to study thylakoids that had lost the ability to evolve oxygen through manganese depletion. In these preparations,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
82
0
8

Year Published

1989
1989
1995
1995

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 32 publications
16
82
0
8
Order By: Relevance
“…The magnetic interaction may consist of both isotropic exchange and anisotropic dipolar components. We note that room temperature measurements of the Yz-lineshape in intact oxygen-evolving PS II preparations show no significant broadening from the interaction with the Mn cluster (39). This is likely due to extremely rapid spin-lattice relaxation of various thermally populated spin states of the Mn cluster at this high temperature which averages out the anisotropic dipolar interaction between the cluster and Yz-.…”
Section: Methodsmentioning
confidence: 75%
“…The magnetic interaction may consist of both isotropic exchange and anisotropic dipolar components. We note that room temperature measurements of the Yz-lineshape in intact oxygen-evolving PS II preparations show no significant broadening from the interaction with the Mn cluster (39). This is likely due to extremely rapid spin-lattice relaxation of various thermally populated spin states of the Mn cluster at this high temperature which averages out the anisotropic dipolar interaction between the cluster and Yz-.…”
Section: Methodsmentioning
confidence: 75%
“…Hoganson and Babcock (1988) have also observed that the amplitude of the Yz signal in O2-evolving preparations differs significantly between the experiments done with dark-adapted samples and those done with repetitively flashed samples, even in the presence of dichloro-benzoquinone and (or) ferricyanide. In steady-state flashing light (2Hz), the Yz signal amplitude has been found to amount to only 40-45% of the amplitude of the Y~ signal (Hoganson and Babcock 1988). Taking into account the small proportion of inactivated centers after each flash of the series, the oscillations with periodicity four of the fluorescence yield measured some milliseconds after each flash of a series have been reported to be correlated with the formation of an S 2 state (Delrieu and Rosengard 1988).…”
Section: Introductionmentioning
confidence: 89%
“…This conclusion is based on the finding that a small proportion of these oxygenevolving centers could become non-functional (6-10%) after each flash of a series (with a repetition rate of 1 Hz), and remain inactivated until dark-adapted (Delrieu and Rosengard 1987, 1988, 1991. Hoganson and Babcock (1988) have also observed that the amplitude of the Yz signal in O2-evolving preparations differs significantly between the experiments done with dark-adapted samples and those done with repetitively flashed samples, even in the presence of dichloro-benzoquinone and (or) ferricyanide. In steady-state flashing light (2Hz), the Yz signal amplitude has been found to amount to only 40-45% of the amplitude of the Y~ signal (Hoganson and Babcock 1988).…”
Section: Introductionmentioning
confidence: 99%
“…An endergonic charge separation occurs between P680 and a pheophytin (Pheo) molecule. Charge recombination of the P(jgo+-PheO-pair is prevented by the following two reactions: 1) a rapid (250-550 ps, Nuijs et al, 1986;Leibl et al, 1989) electron transfer from Pheo-to a nearby plastoquinone molecule known as QA; and 2) the reduction of P680+ by a redox-active tyrosine residue (Yz) within 40-280 ns (Hoganson et al, 1988;Gerken et al, 1988). Reduced plastoquinone (QH2) carries electrons from PSII into the'cytochrome bf complex which then reduces plastocyanin (PC).…”
Section: Lumenmentioning
confidence: 99%